Mastering Autodesk Navisworks 2012 - Dodds, Jason, 1977- (Serious skills., 2011)
"Design, communicate and collaborate with NavisworksMastering Autodesk Navisworks shows you how to best use the amazing Navisworks software. This collaboration tool enables the consolidation of all files connected to a construction project?including file formats such as Revit, SketchUp, ArchiCAD, and others?into one 3D model that all participants can view, share, navigate, and use for visualization and simulation. With the ability to support 60-plus file formats, Naviworks has an eager fan base seeking more information. Using step-by-step tutorials, real-world examples, and hands-on exercises, this thorough guide provides the complete guidance you need to master Navisworks. Introduces you to Navisworks using a workflow approach that mirrors how it is used on real projects from start to finish Explains how to import the 60+ supported file formats, navigate around the merged 3D model, document and annotate it, and coordinate schedules with TimeLiner Delves into the powerful clash detection tool, which warns you if a design will not work in the real world Covers advanced functions such as creating visualizations and using scripting tools Features step-by-step instruction, real-world examples, and downloadable before-and-after tutorial files Mastering Autodesk Navisworks is the ultimate reference on this exciting collaboration and design review software"--